Maturation of phagosomes containing different erythrophagocytic particles in primary macrophages - Santarino, I.B. (2017)
This work was supported by iNOVA4Health-UID/Multi/04462/2013, a program financially supported by FCT through national funds and cofunded by FEDER under the PT2020 Partnership Agreement and FCT to OVV.